IMPLEMENTATION OF DOUBLE MOVING AVERAGE METHOD IN PREDICTION OF OMEGA 3 CHICKEN EGG HARVEST RESULT of PAK DARMO WEB-BASED: Peternakan Pak Darmo, Desa Rejosari, Kecamatan Sugio, Kabupaten Lamongan - Athia Syarif Hidayatullah; Nurul Fuad (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2023)
Eggs are one of the livestock products that help people to get adequate nutrition. In Indonesia, chicken eggs are in great demand, besides being easy to obtain and the price is affordable, Omega 3 chicken eggs are one of the chicken eggs that have very many benefits. However, chicken eggs themselves become a rare staple because the yield of chicken eggs is too little. The main purpose of this application was to forecast or predict the yield of chicken eggs accurately so that it became one of the options for egg supply in the future. Making the application used the Double Moving Average method as a forecasting method. The Double Moving Average was used as an analysis of data on the yield of chicken eggs Omega 3 with the right calculation produced an accurate forecast. Implementation of the application is intended for users starting from filling in data, filling in forecasting movements, and additional features such as recaps. The results of the application are explained from the forecasting results which have a high level of accuracy and a small error rate using the Double Moving Average method.